I.YUSUPOVTÍŃ PROZALÍQ SHÍǴARMALARÍNDA DINAMIKALÍQ FEYILLERDIŃ ÓZGESHELIGI - Shaniyazov, J.U. (SCIENCE and SOCIETY, 2023)
The article analyzes the verbs used in the works of I. Yusupov. Verbs are lexical-semantically divided into several groups and analyzed according to their meanings. The verbs in the narrative language are shown on the examples.